Phosphate Status Affects Phosphate Transporter Expression and Glyphosate Uptake and Transport in Grand Eucalyptus (Eucalyptus grandis). Issue 1 (3rd October 2018) - Pereira, Fernanda Campos Mastrotti; Tayengwa, Reuben; Alves, Pedro Luis Da Costa Aguiar; Peer, Wendy Ann
Abstract: Soluble phosphate availability is a major limiting factor for plant growth, development, and yield. To assure a constant phosphorous supply, plants employ both high- and low-affinity phosphate acquisition mechanisms. Glyphosate is an herbicide widely used throughout the world, and previous studies have suggested that it can be transported across the plasma membrane via phosphate transporters in herbaceous species. The effects of phosphate status on glyphosate uptake were investigated in the tree grand eucalyptus ( Eucalyptus grandis W. Hill ex. Maid.) . Eucalyptus grandis 's putative phosphate transporters showed differential gene expression in leaves and roots in response to phosphate limitation. Overall, the expression of high-affinity phosphate transporters increased in phosphate-limiting treatments, particularly in roots. More [ 14 C]glyphosate was absorbed and translocated in phosphate-limiting plants compared with control plants grown in phosphate-replete treatments. In leaf mesophyll protoplast assays, rapid uptake of [ 14 C]glyphosate into protoplasts was observed, and addition of phosphate to the assays competed with [ 14 C]glyphosate uptake. These data indicate that phosphate transporters represent one mechanism of glyphosate uptake in E. grandis . These results have implications for best management practices for weed control and glyphosate application under phosphate application regimes.